Relationship between age and progesterone receptor expression with presence of central nervous system metastases in breast invasive ductal carcinoma - Eduardo Cambruzzi; Luana R. Gassen; Andrei Reginatto; Andressa Noshang; Fernanda P. Brandão; Larissa R. Roman; Luciana H. Miranda; Karla Lais Pêgas (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACTIntroduction:Breast invasive carcinoma of no special type (NST) is characterized by great morphological heterogeneity, and accounts for about 70%-80% of malignant breast tumors. The main prognostic factors are tumor size, degree of differentiation, and status of axillary lymph nodes. NST represents 15%-18% of central nervous system metastases (CNSm), and generally the response to systemic treatment/chemotherapy is unsatisfactory.Objective:To estimate the association between clinical and pathological findings of NST with CNSm.Method:Clinical data of 171 specimens of lumpectomy/mastectomy with axillary dissection in NST were evaluated, as well as the following pathological variables: tumor size, histological grade, nodal status, expression of estrogen (ER) and progesterone receptors (PR) and human epidermal growth factor receptor 2 (HER-2/neu) oncogene (c-erb B2), and presence of CNSm. The cases of CNSm in NST underwent resection, and the primary site was identified by immunohistochemistry.Results:The prevalence of CNSm was 9.4% (n = 16), and was related to age (p = 0.01), and the expression of PR (p = 0.004). Although cases of NST with CNSm showed correlation with greater tumor size, higher histological grade and nodal metastases, there was no statistical association (p = 0.221, p = 0.224 and p = 0.99, respectively). Expression of ER and c-erb-B2 was not significant between the two groups (p = 0.072 and p = 0.31, respectively).Conclusion:This study showed that younger patients and the expression of RP correlate with the presence of CNSm. The evaluation of specific pathological findings in NST can help establish risk factors and/or clinical parameters associated with the development of CNSm.